Chiral recognition of polysaccharide based CSP for separation of enantiomers and regio isomers of Prasugrel and its related impurities - Vuyyuru Nagireddya , b, G. Vamsi krishnaa, V. Malatia, B.Ramadevib, Y. Ravindra kumara (Journal of Applied Pharmaceutical Science, 2017)
The current study focuses on the efficiency of chiral chromatographic conditions for separation of critical enantiomers and regio-isomeric pairs of Prasugrel, an antiplatelet drug and its related impurities. Totally, 10 chiral compounds were screened and well resolved using Phenominex-LUX-2-Amylose based chiral HPLC column (polysaccharide CSP). Chiral separations were achieved using Isopropanol, ethanol as organic modifiers and trimethylamine (TEA), trifluoro acetic acid (TFA) as polar modifier. Impact assessment for selection of superior chromatographic conditions to achieve best resolution was evaluated by varying column temperatures and concentrations of organic and polar modifiers. Significant enantiomeric separations were achieved with low alcohol and high TFA concentrations as modifiers in mobile phase. With optimized conditions, not only Prasugrel’s enantiomers, two process related impurities (3-floro and 4-floro prasugrel) and major degradant i.e., Des acetyl impurity which exhibits keto-enol tautomerism in solution state were also separated into respective individual enantiomeric forms. Hence, the current work can be implemented for evaluation of chiral impurities of Prasugrel during synthesis as well as in Active Pharmaceutical Ingredient.
Keywords: Chiral stationary phase (CSP), LUX Amylose-2, Prasugrel, Regio isomers, Organic modifiers, photo diode array detector (PDA).